2020
DOI: 10.2337/db20-0772
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Loci and Physiologic Pathways Involved in Gestational Diabetes Mellitus Implicated Through Clustering

Abstract: Hundreds of common genetic variants acting through distinguishable physiologic pathways influence the risk of type 2 diabetes (T2D). It is unknown to what extent the physiology underlying gestational diabetes mellitus (GDM) is distinct from that underlying T2D. In this study of >5,000 pregnant women from three cohorts, we aimed to identify physiologically related groups of maternal variants associated with GDM using two complementary approaches that were based on Bayesian nonnegative matrix factorizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Lipid physiology in pregnancy is complex, as both fetus and placenta play an active role, with enhanced de novo lipogenesis occurring in early pregnancy ( 31-33 ).While de novo lipogenesis is generally considered to be a response to excess dietary carbohydrate ( 34 ), the propensity to increased de novo lipogenesis activity observed in obese pregnant women may have had a causal role in the development of their obesity and hence GDM. Genetic studies of GDM risk have consistently identified associations with genes related to pancreatic beta cell function and insulin synthesis ( 35 ), but a recent report identified a liver lipid-related gene cluster related to GDM ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lipid physiology in pregnancy is complex, as both fetus and placenta play an active role, with enhanced de novo lipogenesis occurring in early pregnancy ( 31-33 ).While de novo lipogenesis is generally considered to be a response to excess dietary carbohydrate ( 34 ), the propensity to increased de novo lipogenesis activity observed in obese pregnant women may have had a causal role in the development of their obesity and hence GDM. Genetic studies of GDM risk have consistently identified associations with genes related to pancreatic beta cell function and insulin synthesis ( 35 ), but a recent report identified a liver lipid-related gene cluster related to GDM ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic analyses reveal that ROBO1 and ROBO2 genes are differentially expressed in islets from T2D patients ( 46 48 ). Using cluster polygenic scores, ROBO2 was also shown to be associated with human gestational diabetes ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been applied recently to GDM in a study that included more than 5000 women in a multi-ancestry cohort [ 76 ]. Initial studies examined the association of the five T2DM clusters with GDM.…”
Section: Genetics Of Gdmmentioning
confidence: 99%
“…The liver-lipid cluster was associated with GDM in the full multi-ancestry cohort, while the other three clusters were not associated with GDM. In a second approach, a subset of the cohort was used to derive five pregnancy-related clusters that were characterized by different glycemic traits and genetic variants [ 76 ]. One cluster that was characterized by postload glucose levels, lower disposition index, and higher adiposity measures was associated with GDM.…”
Section: Genetics Of Gdmmentioning
confidence: 99%